New methods in teaching and learning to produce artworks through cross-disciplinary approach using creativity theory - Sulaiman, Rushana; Samsudin, Mat Redhuan; Ahmad Tarmizi, Mohd Shahrul Hisham; Zahari, Siti Safura; Roslan, Nur Fatiyah; Alias, Suriana; Daud, Noorlida (Universiti Teknologi MARA, Perak, 2025)
The integration of cross-disciplinary knowledge among art students is a new approach in the learning and teaching process. The field of art encompasses various aspects of life that meet the needs of psychology, sociology, and anthropology, playing an important role in meeting the historical needs of human artistic development. This study aims to encourage students to understand the function of interdisciplinary knowledge in the implementation of their art project research. Interpretation becomes more focused and meaningful with the application of various theories and models that are interconnected in a study. Art students need to apply generic skills such as creativity, innovation, and critical thinking to generate new ideas in the production of art products. However, traditional learning and teaching methods are less effective in meeting the needs of interdisciplinary knowledge in the context of art education. Students often face difficulties in generating new ideas that are creative and innovative. The absence of an approach that combines cross-disciplinary knowledge causes the learning process to be unsystematic, less structured, and less focused. This situation hinders students' efforts to achieve their full potential in creating artwork. This study aims to determine new methods in teaching art through a cross-disciplinary approach that can be applied in the production of student artwork, as well as analyse its impact on increasing innovation, skills, and the contribution of new ideas in art projects. This study uses a qualitative approach with an action research design. Data were collected through direct observation throughout the learning process to monitor the progress of the project. In addition, visual and written documentation was obtained from project assignment plans, idea development, critique sessions, consultations, and presentations. Most of the data for this study was collected at the Faculty of Art and Design, UiTM Machang. The findings of the study showed that a cross-disciplinary approach to art teaching can increase student innovation and creativity. Students successfully integrated concepts and techniques from various disciplines to produce more complex, relevant, and competitive artwork. In addition, this approach also strengthens students' problem-solving skills and sparks new innovative ideas. The results of this study introduce a new model based on a more specific and systematic cross-disciplinary approach to improve students' problem-solving abilities and produce a generation of creative and innovative people in art learning.